The Outcome of Percutaneous Nephrolithotomy Using Intravenous Catheter for Obtaining Percutaneous Access as a Treatment for Renal Stone Disease in Children: A Pilot Study - Arslan, Mehmet Serif; Zeytun, Hikmet; Basuguy, Erol; Arslan, Serkan; Aydogdu, Bahattin; Okur, Mehmet Hanifi (Urology Journal, 2016)
Purpose: Using percutaneous nephrolithotomy (PNL), it is easy to reach stones in various parts of the kidney via a single access tract. In the current study, we set out to demonstrate that the intravenous catheter is a safe way to gain renal access, and that PNL is safe in children. Materials and Methods: We retrospectively reviewed the medical records of patients who underwent PNL as a treatment for renal stone disease at our center between September 2013 and December 2014. There were no specific exclusion criteria. We used 14 gauge intravenous catheter for renal access in all cases. Results: Eleven of the 32 patients (34.4%) were female and 21 (65.6%) were male. The mean ± SD patient age was 4.7 ± 3.71 years (9 months-16 years). Six patients (18.7%) were infants less than 1 year of age. Fifteen of the stones (46.8%) were located in the right kidney, and 17 of the stones (53.1%) were located in the left kidney. The average stone size was 13.9 ± 4.8 mm (range, 12-28). The average duration of operation was 69.7 ± 10.4 minutes (range, 50-110), and the average duration of fluoroscopy was 2.21 ± 1.06 minutes (range, 1-6). There were complications in 5 of the cases (15.6%). Conclusion: The access and dilatation stages are quite important. We propose that the intravenous catheter is a safe and inexpensive tool for renal access in PNL in pediatric age group patients.